Star formation in metal-poor gas clouds - Glover, Simon; Clark, Paul C. (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. Observations of molecular clouds in metal-poor environments typically find that they have much higher star formation rates than one would expect base